The Routledge Handbook of Nature-Based Tourism Development - Mandić, Ante; Walia, Sandeep K. (Taylor & Francis, 2023)
art-based methods; participatory design; stakeholder engagement; nature-based site; cultural tourism; cultural sensitivity; sustainability